Kakovost življenja mladostnikov, ki so v obdobju novorojenčka utrpeli hipoksično-ishemično encefalopatijo - Bregant, Tina (Zdravniški vestnik, 2012)
Background: Hypoxic-ischaemic encephalopathy (HIE) during the perinatal periodis a commonly recognized cause of severe, long-term neurological sequelae in children. Milder hypoxia- ischaemia can lead to minor disabilities, which can manifest only later with age-specific cognitive abilities and demands. Methods: We have used prospective, observational study of an inception cohort of 16 adolescents, who had neonatal HIE, compared to a gender- and age-matched control of 16 healthy medical students. Our cohort wasselected from the Slovenian population of neonates, referred to the Pediatric Intensive Care Unit at the University Medical Centre Ljubljana, due to mild and moderate HIE, Sarnat stage 1 and 2. HIE was confirmed by generallyaccepted criteria. We estimated the self-assessed health-related quality of life by using SF-36v2 questionnaire, Rosenberg self-esteem inventory and Unwholesome behaviour questionnaire. Results: Our study included16 adolescents with HIE, 7 girls (43.8 %) and 9 boys (56.3 %), who were born at a mean gestational age of 35.75 weeks (SD = 3.80) and mean birthweight of 2644g (SD = 815), which represents 50th percentile. Mean age was 21.69 years (SD = 0.87). Adolescents with a history of HIE reported a higher number of additional morbidity yet with a good quality of life. Health-related quality of life was rated high: for adolescents with HIE M = 81.9 (SD = 11.2) and for healthy adolescents M = 75.3 (SD = 11.,5); p = 0.112.The adolescents with HIE odsodid not differ from the healthy adolescentsin self-esteem (p = 0.68) and unwholesome behaviours, except for over-eating (p = 0.01). Conclusions: Based on our data of higher morbidity, wepropose that children with mild to moderate HIE, even when discharged as healthy, should be subject to a follow-up. They develop compensatory strategies, which enable them to have a good quality of life. We can hope thattheir compensatory strategies, rather than becoming insufficient when theyreach adulthood, will enable them to have a high quality of life.
Keywords: dolgoročno sledenje; hipoksično-ishemična encefalopatija; kakovost življenja; long-term follow-up; neurology; nevrologija; quality of life; samospoštovanje; self-esteem; SF-36v2 survey; standard of living; unwholesome behaviours; vprašalnik SF-36v2; zdravju škodljiva vedenja